Роль кольорової гами в структурі сайту - Задорожна, В. К.; Вовк, О. В. (ХНУРЕ, 2025)
The work examines the interaction of color scheme and site structure as a key factor influencing user experience. By analyzing examples, we can understand how different approaches to color design and element layout can improve or complicate navigation and content perception. Let's consider the importance of the color scheme of text elements, headings and the interaction of colors between them. How exactly they can strengthen or weaken each other, affecting the result of the user's perception of the site page. When analyzing examples, we can find elements that, under the influence of certain color schemes, will have an impact on the further result.
Keywords: кольорова гама; структура сайту